2020
DOI: 10.1177/1942775120947460
|View full text |Cite
|
Sign up to set email alerts
|

Program Capacity for Redesign in Educational Leadership Preparation

Abstract: Characteristics that contribute to successful redesign and launch of principal preparation programs may be understood collectively as the capacity of those programs. A model of capacity for redesign of principal preparation programs should strike a balance between the technical and professional aspects of teaching and leadership and the cultural and relational aspects of organizations. We surveyed a national sample of program directors and interviewed a purposive sample of those in the midst of redesigning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although a follow-up study using inferential statistics would be necessary to identify significant differences, these qualitative results raise questions about how much autonomy instructors should have to tailor courses to their own preferences and whether educational leadership faculty have the capacity to keep their programs updated. Clement et al (2022) found that principal preparation program redesigns require both (a) a culture of inquiry, collaboration, and adaptiveness; and (b) resources that include funds, support, and expertise to conduct the work. My own experiences with territorial faculty and curriculum development bureaucracy indicate both can be substantial barriers in a field where this work is seldom recognized or rewarded.…”
Section: Discussionmentioning
confidence: 99%
“…Although a follow-up study using inferential statistics would be necessary to identify significant differences, these qualitative results raise questions about how much autonomy instructors should have to tailor courses to their own preferences and whether educational leadership faculty have the capacity to keep their programs updated. Clement et al (2022) found that principal preparation program redesigns require both (a) a culture of inquiry, collaboration, and adaptiveness; and (b) resources that include funds, support, and expertise to conduct the work. My own experiences with territorial faculty and curriculum development bureaucracy indicate both can be substantial barriers in a field where this work is seldom recognized or rewarded.…”
Section: Discussionmentioning
confidence: 99%